Avaliação do efeito trombogênico da perfusão regional intravenosa com gentamicina em equinos - Rafael, Leandro Américo [UNESP]; Rodrigues, Celso Antonio [UNESP]; Evangelista, Felipe Carvalho [UNESP]; Ramires, C. [UNESP]; Rodrigues, Mirian [UNESP]; Pizzigatti, Dietrich [UNESP]; Perri, Sílvia Helena Venturoli [UNESP]; Hussni, Carlos Alberto [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2014)
The distal end of the horse is often affected by septic processes that are difficult to treat. The intravenous regional perfusion of antimicrobials is a treatment option for these processes, increasing the local concentration of the drug using small doses, and is currently widely used, but still presenting various issues. The aim of this study was to evaluate the possible complications of the technique, using gentamicin at a dose of 2.2mg/kg in the cephalic vein of horses. Fifteen healthy horses were assigned to three groups of 5 animals. Group 1, tourniquet group (TG), group 2, tourniquet and 40mL of physiologic saline solution (SPG) and group 3, tourniquet and 2.2mg/kg gentamicin completed to 40mL by the addition of physiologic saline solution (ASG). The perfused limb was evaluated by thermography and ultrasound Duplex color over time. The data were analyzed by Tukey's and Dunnett's method, and the accepted significance level was P<0.05. All groups showed thrombotic score zero and there was no significant difference between groups in the average diameter of the vein and member temperatures. The intravenous regional antibiosis with 2.2mg/kg of gentamicin as a single dose did not affect the development of thrombosis in the cephalic vein.

A extremidade distal dos equinos é frequentemente afetada por processos sépticos de difícil tratamento. A perfusão regional intravenosa de antimicrobianos é uma opção de tratamento para esses processos, pois aumenta a concentração do fármaco no local mediante pequenas doses. Entretanto, apesar de ser muito utilizada recentemente, ainda apresenta várias questões. O objetivo deste trabalho foi avaliar as possíveis complicações da técnica, com o uso da gentamicina na dose de 2,2mg/kg na veia cefálica de equinos. Utilizaram-se 15 equinos hígidos divididos aleatoriamente em três grupos de cinco animais: grupo somente com torniquete (GT), grupo que recebeu 40mL de solução fisiológica (GSF) e grupo que recebeu gentamicina na dose de 2,2mg/kg, acrescida de solução fisiológica até completar o volume de 40mL (GSG). O membro perfundido foi avaliado por termografia e ultrassonografia duplex em cores ao longo do tempo. Os dados foram submetidos à análise pelos testes de Tukey e de Dunnett, e o nível de significância adotado foi de P<0,05. Todos os grupos apresentaram escore trombótico zero, e não houve diferença significativa entre os grupos quanto ao diâmetro médio da veia e da temperatura dos membros. A antibiose intravenosa regional com 2,2mg/kg de gentamicina, em dose única, não acarretou o desenvolvimento de trombose na veia cefálica
Evaluation of intravenous regional perfusion thrombogenic effect with gentamicin in equine
Keywords: perfusão regional; artrite séptica; trombose e cavalos; regional perfusion; septic arthritis; thrombosis and horses